Clinical and microbiological findings of infective endocarditis - Cancan Gursul, Nur; Vardar, Ilknur; Demirdal, Tuna; Gursul, Erdal; Ural, Serap; Yesil, Murat (The Journal of Infection in Developing Countries, 2016)
Introduction: Infective endocarditis (IE) is an infection that develops on the endothelial surface of the heart. Endocarditis is a major problem for the clinicians despite of the developments in diagnostic, surgical, and medical treatment methods. In this study, we aimed to evaluate symptoms, laboratory findings, treatment options, and clinical endpoint of the patients who were diagnosed with IE in a tertiary healthcare organization according to the literature data. Methodology: Between January 2006 and March 2013, 80 IE patients who were diagnosed and treated in accordance with modified Duke criteria were enrolled in the study. Demographic features, symptoms, and laboratory and echocardiographic findings were recorded after reviewing the patient files. Results: The mean age of the patients was 51.3 ± 16.0, and IE was more common in men (n = 56; 70%). Of 41 patients who had positive blood cultures, 20 patients had Staphylococcus spp. (48.7%) and 8 patients had Streptococcus spp. (19.5%). Brucella spp. was isolated from 5 patients (12.2%). While 48.7% (n = 39) of the patients had cardiac complications, 22 patients (27.5%) had embolic complication. Hospital mortality was observed in 20 patients (15%). Conclusions: In our patients, endocarditis was seen at a young age, and staphylococci were the most frequently isolated microorganism from blood culture. There were more patients with Brucella endocarditis compared to the general population. Complications are frequently seen in the course of endocarditis, and they cause problems for the clinicians during follow ups due to the high mortality rate of IE.